SYSTEMATIC LITERATURE REVIEW: ANALISIS LEAN SIX SIGMA UNTUK MENINGKATKAN EFISIENSI PROSES PRODUKSI DI INDUSTRI MANUFAKTUR - Florencia Charlene Teng; Lithrone Salomon (Jurnal Mitra Teknik Industri, 2026)
The purpose of this paper is to explore the topic of Lean Six Sigma (LSS) application in the manufacturing sector and to identify existing research gaps within this field. The study employed a Systematic Literature Review (SLR) methodology. The database utilized for identifying relevant literature was the Scopus website. The findings are presented through a detailed quality assessment of the retrieved articles according to the defined research scope. A total of 26 relevant articles were identified, with the inclusion criteria requiring them to be published and registered in Scopus-indexed international journals. The systematic literature review applied in this paper allows for the regular and thematic highlighting of emerging trends and challenges in Lean Six Sigma, thereby facilitating future work as LSS continues to evolve.